Retraction: Evaluation of carcinogenic effects of electromagnetic fields (EMF) - Bakir Mehić (Biomolecules & Biomedicine, 2010)
The Editor-in-chief of the Bosnian Journal of Basic Medical Sciences has decided to retract the article from Bayazit V et al. [1] entitled as: “Evaluation of carcinogenic effects of electromagnetic fields (EMF)” published in Bosn J Basic Med Sci. 2010 Aug;10(3):245-50.After the editorial office was alerted of possible plagiarism in the article, it conducted thorough investigation and concluded that the article apparently represents plagiarized material from two World Health Organization reports, one European Commission report and other sources. Since this is considered scientific plagiarism and scientific misconduct, Editor-in-chief has decided to withdraw the article. The authors have agreed with the editorial office decision.